2020
DOI: 10.5194/egusphere-egu2020-21951
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assimilation of Sentinel-2 Leaf Area Index Data into a Physically-Based Crop Growth Model for Yield Estimation

Abstract: <p>The work is based on a previously published study with the aim to further analyse the results obtained. Remote sensing data, crop growth models, and optimization routines constitute a toolset that can be used together to map crop yield over large areas when access to field data is limited. In this study, Leaf Area Index (LAI) data from the Copernicus Sentinel-2 satellite were combined with the Environmental Policy Integrated Climate (EPIC) model to estimate crop yield. The experiment was imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The elements in transfer matrix C(cij) and quasi-optimal uniform matrix C * (cij * ) need to meet Equation (9) and (10).…”
Section: =1mentioning
confidence: 99%
See 1 more Smart Citation
“…The elements in transfer matrix C(cij) and quasi-optimal uniform matrix C * (cij * ) need to meet Equation (9) and (10).…”
Section: =1mentioning
confidence: 99%
“…It is reported that there are approximately 32 types of CGM combining multiple data sources and methods to monitor the potato yield under conditions of water, nitrogen fertilizer, and CO2 atmospheric levels [8]. However, the difficulty of obtaining large amounts of input data is one of the major limitations of the widespread employment of models due to their complexity [9][10][11]. Furthermore, field investigation, another traditional method, is a destructive estimation way.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that there are approximately 32 types of CGM combining multiple data sources and methods to monitor the potato yield under conditions of water, nitrogen fertilizer and CO 2 atmospheric levels [8]. However, the di culty of obtaining large amounts of input data is one of the major limitations of the widespread employment of models due to their own complexity [9][10][11]. Furthermore, eld investigation, another traditional method, is a destructive estimation way.…”
Section: Introductionmentioning
confidence: 99%